Traumatic skin loss from the mail genitalia - Hrbatý, J; Molitor, M (Acta chirurgiae plasticae, 2001)
The authors present the case-report of a 35-year-old patient with traumatic losses of the scrotum and penis. For acute and final treatment, they used a free transfer of a fasciocutaneous flap. They selected a sensitive Chinese flap for reconstruction of the scrotum; the penis was treated by transplantation using dermoepidermal grafts. The patient recovered without major complications. In the authors' opinion, the advantage of this method, as compared with other methods, is the almost normal appearance of the scrotum and the normal physiological site of the testes. Sexual intercourse was resumed after less than four months.
Keywords: výsledek terapie; skrotum; chirurgické laloky; Scrotum; mužské pohlaví; tupá poranění; Surgical Flaps; Treatment Outcome; dospělí; Humans; Wounds, Nonpenetrating; Adult; Skin; penis; kůže; Penis; lidé; Male